2010
DOI: 10.1105/tpc.109.071811
|View full text |Cite
|
Sign up to set email alerts
|

Expression of a Low CO2–Inducible Protein, LCI1, Increases Inorganic Carbon Uptake in the Green Alga Chlamydomonas reinhardtii    

Abstract: Aquatic photosynthetic organisms can modulate their photosynthesis to acclimate to CO 2 -limiting stress by inducing a carbon-concentrating mechanism (CCM) that includes carbonic anhydrases and inorganic carbon (Ci) transporters. However, to date, Ci-specific transporters have not been well characterized in eukaryotic algae. Previously, a Chlamydomonas reinhardtii mutant (lcr1) was identified that was missing a Myb transcription factor. This mutant had reduced lightdependent CO 2 gas exchange (LCE) activity wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
68
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 91 publications
(70 citation statements)
references
References 46 publications
1
68
1
Order By: Relevance
“…Some of these LCI genes, such as CAH3, LCI1, LCIA, LCIB, and HLA3, reportedly play important roles in the C. reinhardtii CCM (Galván et al, 2002;Wang and Spalding, 2006;Duanmu et al, 2009aDuanmu et al, , 2009bOhnishi et al, 2010), and the function of others, such as CCP1, CCP2, and LCIC, in the CCM also has been implicated (Pollock et al, 2004;Wang and Spalding, 2006;Yamano et al, 2010). However, only 53 of 106 previously reported LCI genes were supported as L-CO 2 or VL-CO 2 upregulated DE genes in this study.…”
Section: Comparison With Previously Reported Lci Genescontrasting
confidence: 50%
See 1 more Smart Citation
“…Some of these LCI genes, such as CAH3, LCI1, LCIA, LCIB, and HLA3, reportedly play important roles in the C. reinhardtii CCM (Galván et al, 2002;Wang and Spalding, 2006;Duanmu et al, 2009aDuanmu et al, , 2009bOhnishi et al, 2010), and the function of others, such as CCP1, CCP2, and LCIC, in the CCM also has been implicated (Pollock et al, 2004;Wang and Spalding, 2006;Yamano et al, 2010). However, only 53 of 106 previously reported LCI genes were supported as L-CO 2 or VL-CO 2 upregulated DE genes in this study.…”
Section: Comparison With Previously Reported Lci Genescontrasting
confidence: 50%
“…Two CIA5-regulated genes encoding candidate transporters have been implicated in C i transport across the plasma membrane: high light-induced gene3 (HLA3) encodes a putative ATP binding cassette type transporter and is induced under low CO 2 conditions, and knockdown of its expression impairs photosynthesis, C i uptake, and growth in alkaline conditions (Duanmu et al, 2009a). LCI1 encodes a plasma membrane protein reported to increase C i uptake in LCR1 mutants when expressed transgenically (Ohnishi et al, 2010). Two Rhesus-like proteins, RHP1 and RHP2, also are predicted to be plasma membrane located (Yoshihara et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…However, if LCIA does function as a channel to facilitate passive entry of HCO 3 2 into the chloroplast, it would have to depend on the activity of plasma membrane Ci transporters (e.g. HLA3 and LCI1; Duanmu et al, 2009a;Ohnishi et al, 2010) to generate a sufficiently high HCO 3 2 concentration in the relatively small volume between the plasma membrane and chloroplast envelope to establish a HCO 3 2 concentration gradient sufficient to overcome the electrical gradient and push HCO 3 2 across the inner envelope. An LCIA channel would also have to be highly regulated to prevent reversed flow when the HCO 3 2 gradient was not favorable for uptake.…”
Section: Function Of Lcia In CI Uptakementioning
confidence: 99%
“…Some areas of uncertainty regarding key features of the microalgal CCM remain to be addressed. First, Ci, including the charged species, bicarbonate (HCO 3 reach Rubisco, yet the roles, if any, of proposed and confirmed Ci transporters, including the plasma membrane proteins HLA3 and Limiting CO 2 Inducible1 (LCI1) and the chloroplast envelope proteins LCIA (NAR1.2), CCP1, and CCP2 (Im and Grossman, 2002;Miura et al, 2004;Pollock et al, 2004;Mariscal et al, 2006;Duanmu et al, 2009a;Ohnishi et al, 2010), in acclimation and Ci uptake under different limiting CO 2 conditions are not yet clearly defined. Second, previous physiological studies have demonstrated that active uptake of both CO 2 and HCO 3 2 occurs in C. reinhardtii (Moroney and Tolbert, 1985;Sültemeyer et al, 1989), but the molecular components and the underlying mechanism responsible for active CO 2 uptake are still largely unknown.…”
mentioning
confidence: 99%
“…Key components, which have been found recently, for a pyrenoid-based CCM, LCIB/C, were described and a CO 2 recapturing hypothesis by LCIB/C complex surrounding the pyrenoid was proposed in the review. Also, candidate HCO 3 -transporter proteins, required for transport across the plasma membrane, chloroplast envelope, and the thylakoid membranes, and a possible CO 2 channel, the Rhesus factor, HLA, were described (one of those, LCI1, has now been shown to be HCO 3 -transporter; Ohnishi et al 2010). The pyrenoid forming factor LCIB/C was found by the analysis of pmp1 and ad1 mutants of C. reinhardtii, which are unable to grow at air-level CO 2 but able to grow under very low CO 2 conditions.…”
mentioning
confidence: 99%